2018
DOI: 10.1159/000486536
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: Classic and Novel Actions

Abstract: Background: Classically, vitamin D has been implicated in bone health by promoting calcium absorption in the gut and maintenance of serum calcium and phosphate concentrations, as well as by its action on bone growth and reorganization through the action of osteoblasts and osteoclasts cells. However, in the last 2 decades, novel actions of vitamin D have been discovered. The present report summarizes both classic and novel actions of vitamin D. Summary: 1,25(OH)2 vitamin D, the active metabolite of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
318
2
25

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(346 citation statements)
references
References 45 publications
1
318
2
25
Order By: Relevance
“…Vitamin D plays a role in calcium and phosphorus metabolism, thus contributing to bone growth and reorganisation. In addition, vitamin D plays a role in reducing oxidative stress, antimicrobial defence, immunoregulation, anti‐inflammation, anticancer properties, neuroprotective factors and child development …”
mentioning
confidence: 99%
“…Vitamin D plays a role in calcium and phosphorus metabolism, thus contributing to bone growth and reorganisation. In addition, vitamin D plays a role in reducing oxidative stress, antimicrobial defence, immunoregulation, anti‐inflammation, anticancer properties, neuroprotective factors and child development …”
mentioning
confidence: 99%
“…Current vitamin D analysis has focussed on measuring circulating vitamin D metabolites. However, most of the vitamin D actions occur within tissues and cell targets . Matrix‐assisted laser desorption/ionisation (MALDI)‐mass spectrometry imaging (MSI) is a technique that enables regional mapping/imaging of metabolites on tissue surfaces .…”
Section: Analytical Approaches For Vitamin D Analysismentioning
confidence: 99%
“…However, most of the vitamin D actions occur within tissues and cell targets. 41,[187][188][189] Matrix-assisted laser desorption/ionisation (MALDI)-mass spectrometry imaging (MSI) is a technique that enables regional mapping/imaging of metabolites on tissue surfaces. 190 Method development and applications of MALDI-MSI for vitamin D tissue analysis are limited.…”
Section: Vitamin D Conjugationmentioning
confidence: 99%
“…Recently, it has been reported that vitamin D metabolites naturally pass through the blood-brain barrier and they find easy access to neuronal and glial cells. Therefore, vitamin D plays significant role in neurological/neuromuscular disorders in addition to its antiaging property 37 .…”
Section: Ongoing Research and Future Directionsmentioning
confidence: 99%